Inside financial conglomerates: Effects in the Hungarian pension fund markets - Borbála Szüle (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2003)
Financial conglomerates have evolved in many countries with a developed financial system, their presence and impact are however quite diverse in these economies. Since this phenomenon raises interesting questions about the stability and efficiency of the financial system as well, it is worth examining first of all what kind of effects the participation in a group formed by different financial firms has on the participating institutions. Motivated by this reason in this paper I examine some hypotheses concerning the impact of financial conglomerates in the Hungarian pension fund market. Based on the common view present in the related literature more effective operation and better performance of the participating funds may be assumed. In contrast to this, the results are mixed: an overall evidence in support of the greater effectiveness and better performance of the participating funds could not be found, although there are some features that show an impressive advantage of the participants in financial conglomerates.
Keywords: 330; Finanzdienstleistung; Finanzsektor; Konglomerat; Pensionsfonds; Rentabilität; Ungarn